An investigation into the factors effective in the consent of families with brain-dead patients candidates for organ donation in Isfahan, Iran in 2012-13 - Maryam Khalifehsoltani Khajooei; Fereshteh Zamani; Asieh Maghami Mehr (Wolters Kluwer Medknow Publications, 2016)
Background: Studies have shown that, with regard to social, cultural, and institutional contexts, several factors affect family decision-making on organ donation. This study aimed to investigate the effective factors in organ donation by family members with brain-dead patients. Materials and Methods: This was a descriptive-comparative study in which a researcher-made questionnaire was used to collect data. The reliability of the questionnaire was obtained as 0.81 using Cronbach's alpha. The study sample consisted of 85 members of families with brain-dead patients in Isfahan, Iran in 2012-13. The collected data were analyzed using the Statistical Package for the Social Sciences version 20.0, and the level of significance was considered as <0.05. Results: The obtained results indicated that factors such as age, marital status, level of education, and cause of brain death did not have any effect on their families consent, whereas factors such as gender, duration of hospitalization, having an organ donation card, personal view of the brain-dead patient, and the number of patient's children had a significant relationship with the consent on organ donation. In addition, the care and treatment team were effective in family decisions regarding organ donation. Conclusions: In general, the necessary culture and increasing the population awareness and their knowledge can be a positive step in this regard and may bring about an easy and rapid acceptance of organ donation by the involved families.